Genes required for the synthesis of heptose-containing oligosaccharide outer core extensions in Haemophilus influenzae lipopolysaccharide. - Hood, D; Deadman, M; Engskog, M; Vitiazeva, V; Makepeace, K; Schweda, E; Moxon, R (2010)
Heptose-containing oligosaccharides (OSs) are found in the outer core of the lipopolysaccharide (LPS) of a subset of non-typable Haemophilus influenzae (NTHi) strains. Candidate genes for the addition of either l-glycero-d-manno-heptose (ld-Hep) or d-glycero-d-manno-heptose (dd-Hep) and subsequent hexose sugars to these OSs have been identified from the recently completed genome sequences available for NTHi strains. losA1/losB1 and losA2/losB2 are two sets of related genes in which losA has homology to genes encoding glycosyltransferases and losB to genes encoding heptosyltransferases. Each set of genes is variably present across NTHi strains and is located in a region of the genome with an alternative gene organization between strains that contributes to LPS heterogeneity. Dependent upon the strain background, the LPS phenotype, structure and serum resistance of strains mutated in these genes were altered when compared with the relevant parent strain. Our studies confirm that losB1 and losB2 usually encode dd-heptosyl- and ld-heptosyl transferases, respectively, and that losA1 and losA2 encode glycosyltransferases that play a role in OS extensions of NTHi LPS.